DYNAMIC MELTING OF THE PRECAMBRIAN MANTLE: EVIDENCE FROM RARE EARTH ELEMENTS OF THE AMPHIBOLITES FROM THE NELLORE-KHAMMAM SCHIST BELT, SOUTH INDIA - Kumar K.V.; Narsimha Reddy M.; Leelanandam C. (My University, 2006)
The Nellore-Khammam Schist Belt (NKSB) in South India is a Precambrian greenstone belt sited between the Eastern Ghats Mobile Belt (EGMB) to the east and the Cratonic region to the west. The belt contains amphibolites, granite gneisses and metasediments including banded iron formations. Amphibolites occurring as dykes, sills and lenses - in and around an Archaean layered complex - form the focus of the present study. The amphibolites are tholeiitic in composition and are compositionally similar to Fe-rich mafic rocks of greenstone belts elsewhere. The NKSB tholeiites show highly variable incompatible trace element abundances for similar Mg#s, relatively constant compatible element concentrations, and uniform incompatible element ratios. Chondrite-normalized REE patterns of the tholeiites range from strongly LREE depleted ((La/Yb) N = 0.19) to LREE enriched ((La/Yb) N = 6.95). Constant (La/Ce) N ratios but variable (La/Yb) N values are characteristic geochemical traits of the tholeiites; the latter has resulted in crossing REE patterns especially at the HREE segment. Even for the most LREE depleted samples, the (La/Ce) N ratios are > 1 and are similar to those of the LREE enriched samples. There is a systematic decrease in FeO t, K 2O and P 2O 5, as well as Ce and other incompatible elements from the LREE enriched to the depleted samples without any variation in the incompatible element ratios and Mg#s. Neither batch and fractional melting, nor magma chamber processes can account for the non-correlation between the LREE enrichment and HREE concentrations. We suggest that dynamic melting of the upper mantle is responsible for these geochemical peculiarities of the NKSB tholeiites. Polybaric dynamic melting within a single mantle column with variable mineralogy is the likely mechanism for the derivation of NKSB tholeiitic melts. It is possible that the NKSB tholeiites are derived from a source with higher FeO/MgO than that of present day ridge basalts. © Springer-Verlag 2006.
Keywords: AMPHIBOLITE; DYNAMIC MELTING; GEOCHEMISTRY; INDIA; NELLORE-KHAMMAM SCHIST BELT; RARE EARTHS; Палеозой::Кембрийская; Paleozoic::Cambrian